ANALISIS KINERJA PUTAR BALIK (U-TURN) DI RUAS JALAN PAHLAWAN KOTA SAMARINDA - IRAWAN, DERRY (KURVA S JURNAL MAHASISWA, 2014)
Growth in the number of vehicle wheels 2 (R2) and 4-wheel vehicles (R4) in Samarinda City continues to increase every year. However, it is not accompanied by increments of roads or road capacity significantly. Consequently, the delay often occurs especially during rush hour (peak hour). This is because the need for the movement of traffic is greater than the level of service of the existing road infrastructure. One of the bottlenecks which are felt by people in Samarinda occurred at Jalan Pahlawan that its land use is commercial environment that is the center of the market activities as well as some educational facilities. Facilities reverse the direction of rotation (U-Turn) in Jalan Pahlawan adjacent to the educational facilities market activity and this causes the vehicle speed when the vehicle stops what did reverse the direction of rotation (U-Turn). The presence of U-Turn This causes delays to vehicles traveling in the direction of the straight.The intent of this research was to determine the performance due to turn around the direction (U-turn) against traffic in JL. Pahlawan SamarindaÂ Â Â Â Â Â Â Â Â Â Â Â Â Â  Results of the analysis of a U-turn (U-Turn) in two (2) points Jalan Pahlawan Samarinda namely;1. The time between the vehicle with another vehicle (time headway) on average for motorcycles (MC) of 0.501 seconds and the light vehicle (LV) of 6.059 seconds.2. When turning the vehicle will perform round-turn (U-Turn) average of motorcycles (MC) of 5.674 seconds and the light vehicle (LV) of 9.602 seconds3. Service queues round-turn (U-Turn) using the First In First Out (FIFO) averaging motorcycles (MC) amounted to 12.768 and light vehicle (LV) of 1,670 where Ï> 1.0 that occurred queues round reverse direction (U-Turn).